127. Voluntary Breath Hold (VBH) technique versus free breath standard technique (FB), in radiotherapy treatment of left side breast cancer. First results in our center. (December 2018) - Pinna, F.; Bona, R.; Poggiu, A.; Tamponi, M.; Soddu, S.; Dedola, M.F.; Marini, P.
Abstract: Purpose: Recent studies on patients undergoing radiotherapy of left side breast demonstrate that late heart damage is directly related to the average doses to the entire organ, apparently without threshold[1], and the maximum doses to its principal arteries[2] . The VBH technique makes it possible to reduce the dose to the heart compared to FB[3] . Methods and materials: This technique can be done in three different ways: (a) with active breathing control devices, based on spirometric systems; (b) with respiratory gating based on the visualization, by infrared camera, of the reflecting markers of a phantom placed on the chest of the patient; (c) with tattoo visual control based technique that identifies the patient's position in deep inhale, both in simulation CT scan and in the treatment phase. While the first two techniques require investment in equipment and accessories, the third, adopted by our center, is achievable with what is normally available in a radiotherapy department. For the first 9 patients, treatment plans were implemented in both FB and VBH. Results: The results obtained, reported in Table 1, are encouraging. At equal coverage of target and dose to the lung, there is a noticeable decrease in dose to the heart and to the left anterior descending artery. Conclusions: The adopted technique is a valid aid to the radiotherapy of breast cancer in selected patients.